CHARACTERIZATION AND THERMAL STUDY OF SEWAGE SLUDGE FROM THE MUNICIPAL WASTEWATER TREATMENT PLANT OF EL EULMA, ALGERIA - ISSAM BOUDRAA; HASSINA BOUGHERARA; BRAHIM KEBABI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The continuous produce of sewage sludge generated by the treatment of wastewater in wastewater treatment plants poses a serious environmental problem. The characterization of sewage sludge before its reuse in safe way becomes very important. The aim of this study is the characterization of sludge and calcined sludge in different temperatures in the range of 200 °C - 1100 °C. Qualitative and quantitative analysis were achieved using X-ray diffraction (XRD) and X-ray fluorescence (XRF). Thermal behavior of sludge was studied using thermo gravimetric analysis (TGA), differential thermal analysis (DTA) and differential scanning calorimetry (DSC). Loss in mass, carbonates rate, pH, chemical oxygen demand (COD) and nitrate contents are also measured. Results show that major mineral constituents in our sludge and calcined sludge are, Al2O3, SiO2, CaCO3 and Fe2O3. Thermal behavior of sludge indicates three important losses in mass, first with a value of 8.24 % in temperature lower than 250 °C, the second with a value of 43.79 % between 230 °C and 700 °C and above 700 °C until 1100 °C a loss of 13.77 %. pH measurements values of different calcined samples are in the range from